Experimental Comparison of Integrated Transformers in a 28 nm Bulk CMOS Technology - Rimmelspacher, Johannes; Breun, Sascha; Werthof, Andreas; Geiselbrechtinger, Angelika; Weigel, Robert; Issakov, Vadim (European Microwave Conference 2018, 2018)
This paper presents a systematic comparison of integrated transformer structures realized in a 28 nm bulk CMOS technology and characterized up to the millimetre-wave frequencies. First, the rectangular versus octagonal coil shapes are compared. Next, different transformer routing realizations using various magnetic coupling mechanisms are examined: interleaved transformers using lateral coupling, stacked ones using vertical coupling and symmetrical transformers using the combination of both coupling mechanisms. Finally, the comparison is repeated for different turn ratios: 1:1, 1:2 and 2:2. The electrical properties of the transformers, such as self-inductance, quality factor, self-resonance frequencies and mutual coupling coefficient are analysed. Advantages and disadvantages of these structures are discussed with regard to their applicability in various active circuits. One of the main targets is to obtain the best transformer’s electrical parameters for a given fixed area and given metallization option. The structures are measured up to 70 GHz. On-chip interconnects are de-embedded and the devices are compared to the models simulated by EM field solver.<br
Keywords: millimeter-wave; CMOS; transformers